Managing Investment Banks: an Introduction - Seethapathi , K; Suryanarayana, A; Subbulakshmi, V ed. (India : ICFAI University, 2003)
Business
Keywords: Managing Investments; Investments; Banks; Investments Banks; Banking Industry; Organigational Design; Operations Management; Oompensation Policies; Skills for Bankers